Morphological and Morphometric Study of Papillary Muscles in Adult Cadaveric Hearts: A Cross-sectional Study from Central India - Geslin Varghese; Mayura Setiya (Journal of Clinical and Diagnostic Research)
Introduction: A normal Atrioventricular (A-V) valve complex of the human heart comprises the A-V ring, cusps, chordae tendineae, and papillary muscles. Papillary muscles are small pillar-like myocardial structures that stabilise the position of the tricuspid and bicuspid valves. A detailed understanding of normal anatomy, as well as its possible variations, can help surgeons in various surgical repairs of valve prolapse and regurgitation involving the papillary muscles. Aim: To review the morphology of papillary muscles in both ventricles. Materials and Methods: This descriptive cross-sectional study was carried out on 60 formalin-fixed adult cadaveric heart specimens collected from the Department of Anatomy of Netaji Subhash Chandra Bose Medical College, Jabalpur, Madhya Pradesh, India from January 2023 to December 2023. These human hearts were carefully dissected to open both the right and left ventricles and expose the anterior, posterior, and septal papillary muscles. Different morphological features of the papillary muscles present in both ventricles were documented and photographed. The details collected were entered into an Excel sheet and analysed. Results: In the present study, there were approximately 33 male adult human hearts and 27 female adult human hearts. The anterior and posterior papillary muscles were present in both the ventricles of all the hearts; however, the right septal papillary muscle was present in only 13 specimens (21.66%). The lengths of the right (15.22±4.642 mm) and left (19.61±5.24 mm) anterior papillary muscles were longer than those of the remaining papillary muscles. The breadths of the right (6.243±2.144 mm) and left (9.992±3.972 mm) anterior papillary muscles were wider compared to other papillary muscles. The anterior and posterior muscles predominantly appeared conical (100%), while the septal muscle was chiefly merged with the septal wall (83.3%). Conclusion: In-depth knowledge of the normal and variable anatomy of the papillary muscles will help cardiac surgeons determine appropriate surgical repair procedures for the valvular complex and helps in dealing with pathological conditions such as valve prolapse or regurgitation.